Benefit of adjuvant chemotherapy in high-risk colon cancer: a 17-year population-based analysis of 6131 patients with union for international cancer control stage II T4N0M0 colon cancer - Teufel, Andreas; Gerken, Michael; Fürst, Alois; Ebert, Matthias; Hohenthanner, Ina; Klinkhammer-Schalke, Monika (European journal of cancer, 2020)
Background - The benefit of adjuvant chemotherapy in Union for International Cancer Control (UICC) stage III colon cancer has been demonstrated in numerous studies. While adjuvant chemotherapy is generally not recommended in stage II patients, its role in high-risk UICC stage II disease (e.g. T4 tumours) remains controversial. - Methods - The present population-based multicenter cohort study investigated the influence of adjuvant chemotherapy on survival and recurrence rates in high-risk UICC stage II T4N0M0 tumours. Based on an anonymised nationwide ADT data set from 31 clinical cancer registries, we identified a total of 6651 patients with a T4 tumour of the colon, of whom 6131 were eligible for survival analysis. A matched-pair analysis based on propensity scores (PSM) was performed with a subset of 3986 patients. - Results - Multivariable analyses demonstrated a significant benefit of adjuvant chemotherapy for overall survival (OS) (hazard ratio [HR]: 0.711, 95% confidence interval [CI]: 0.643-0.785, p < 0.001), cumulative recurrence rate (HR: 0.780, 95% CI: 0.681-0.893, p < 0.001), and recurrence-free survival (HR: 0.715, 95% CI: 0.652-0.785, p < 0.001) further confirmed by the matched-pair cohort. - Conclusion - This large and representative study demonstrated a significant advantage of adjuvant chemotherapy for patients with T4 UICC stage II colon cancer in terms of OS, recurrence rate, and relapse-free survival. Based on these results, adjuvant chemotherapy should be recommended for these patients.
Gesehen am 05.01.2026